1966
DOI: 10.7883/yoken1952.19.97
|View full text |Cite
|
Sign up to set email alerts
|

On the Delayed Pupation of the Fleshfly, Sarcophaga Peregrina Robineau-Desvoidy

Abstract: The larvae of Sarcophaga peregrine do not pupate in a wet condition. If they are placed in a glass vessel containing a certain amount of water, their pupation delays for 100 hr or more. The cause of this delayed pupation is neither a direct action of water to their integument nor disturbance of respiration, because the pupation takes place even in a wet vessel, if they have been previously exposed to a dry situation for a certain period.The mature larvae transferred into a dry vessel from a wet one always pupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…The flesh fly (Sarcophaga peregrina) was reared by the method of Ohtaki [ 5 ] . The physiological age of the insect was controlled easily by wet/dry treatment.…”
Section: Animalsmentioning
confidence: 99%
“…The flesh fly (Sarcophaga peregrina) was reared by the method of Ohtaki [ 5 ] . The physiological age of the insect was controlled easily by wet/dry treatment.…”
Section: Animalsmentioning
confidence: 99%
“…In flesh flies, pupariation is inhibited when mature larvae are subjected to wet conditions (water treatment), but their development resumes after the larvae were transferred to dry conditions (Ohtaki, 1966;Moribayashi et al, 1996Moribayashi et al, , 2002Yoder et al, 2006). Ohtaki (1986) and Moribayashi et al (1992) showed that the terminal organ located at the anterior end of the first segment of the larval body recognizes water, and this organ then transmits a signal to prevent the release of ecdysteroids that promote pupariation.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae were held under these conditions for 3 days at 25°C with frequent (3-5 times/day) water changes. This "wet" treatment temporarily inhibits the release of ecdysteroids until the larvae are placed in dry conditions, thereby synchronizing pupariation (Ohtaki, 1966).…”
Section: Insect Rearingmentioning
confidence: 99%